Toward Low-Cost and Sustainable Supercapacitor Electrode Processing: Simultaneous Carbon Grafting and Coating of Mixed-Valence Metal Oxides by Fast Annealing - Malaie, Keyvan; Ganjali, Mohammad Reza; Soavi, Francesca (Frontiers in Chemistry, 2019)
There is a rapid market growth for supercapacitors and batteries based on new materials and production strategies that minimize their cost, end-of-life environmental impact, and waste management. Herein, mixed-valence iron oxide (FeOx) and manganese oxide (Mn3O4) and FeOx-carbon black (FeOx-CB) electrodes with excellent pseudocapacitive behavior in 1 M Na2SO4 are produced by a one-step thermal annealing. Due to the in situ grafted carbon black, the FeOx-CB shows a high pseudocapacitance of 408 mF cm2 (or 128 F g−1), and Mn3O4 after activation shows high pseudocapacitance of 480 mF cm2 (192 F g−1). The asymmetric supercapacitor based on FeOx-CB) and activated-Mn3O4 shows a capacitance of 260 mF cm2 at 100 mHz and a cycling stability of 97.4% over 800 cycles. Furthermore, due to its facile redox reactions, the supercapacitor can be voltammetrically cycled up to a high rate of 2000 mV s-1 without a significant distortion of the voltammograms. Overall, our data indicate the feasibility of developing high-performance supercapacitors based on mixed-valence iron and manganese oxide electrodes in a single step.